Regulating halal food consumption: Malaysian scenario - A. Rahman, Aspalella (Global Academic Excellence, 2018)
Malaysia passed several laws to regulate the halal food industry. Effective implementation of the laws is vital to ensure that halal food producers comply with the obligations under the laws and more importantly to enhance the Muslim consumers’ trust in halal food products. The aim of this paper is to examine whether the existing halal laws provide sufficient protection for Muslim consumers. By utilizing a legal research method, this paper analyses the scope and provisions of the relevant laws that govern all matters relating to halal food products. This includes the Trade Description Act 2011, Food Act 1983, Animal Act 1953 (Revised 2006) and Consumer Protection Act 1999. Any shortcomings and gaps in the laws were analyzed in depth. It is submitted that the government has enacted comprehensive laws to regulate the halal food consumption in Malaysia. Indeed, the laws provide sufficient protection to Muslim consumers. However, apart from the unscrupulous business practice, numerous reports on the manipulation of the laws by the food industry clearly show that there are some weaknesses in the implementation and enforcement of Halal laws.